ANALISIS PEMBUBARAN PARTAI POLITIK OLEH MAHKAMAH KONSTITUSI - Hidayat, Bagaskara Rahmat; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2024)
Since this authority was given to the constitutional court, the Constitutional Court itself has never tried a case regarding the dissolution of a political party. Seeing this situation, there is an assumption that authority is useless, which is considered reasonable considering the cases of KKN that mostly happen to a political party, but because of the pretext that the